DESIGNING AN IDEAL MODEL FOR THE INDONESIA SOCIAL SECURITY ADMINISTRATION BODY (BPJS) RELATED TO HEALTH FUND MANAGEMENT - Djuwityastuti Djuwityastuti; Wida Astuti (Faculty of Law, Universitas Sebelas Maret, 2017)
Establishment of the Social Security Administration Body (BPJS) is one manifestation of the nation goals in achieving certainty in protection and social welfare for all citizens. By studying legal foundation as the legality of the establishment of BPJS relating to governance of social security in some countries, the fact shows that the institutional body of BPJS still has some drawbacks. This research is funded by the Ministry of Research, Technology, and Higher Education, the article presents some ideal forms of institutional body of BPJS in relation with the fund management and development for health social security.